As ações de fomento no processo de gestão do museu da Universidade Federal do Pará - XAVIER, Vitor Nonato (2019)
The objective of this work is to promote the management of the Museum of the Federal University of Pará (MUFPA), its objective is to present the development actions carried out in the museum's daily life of this University museum. The specific objective is about the critical reflection of these actions to attract resources to the museum, considering the meanderings of the public policies of the museum sector at the federal level and the principles established in the national museum policy encouraged in 2003 in Brazil. The research theme is museum management and the emphasis on development, where the applied methodology consisted of bibliographical reviews, documentary research, analysis and interpretation process through a case study with the purpose of collecting data in the administrative structure of the organ for the obtaining information on the fomentation actions carried out by him, based on the premises stipulated by the National Museums Policy and the laws that deal with the Statute of Museums, its dispositions arranged in the Brazilian Institute of Museums (IBRAM) of the Ministry of Citizenship. Another area ofanalysis is the Ministry of Education, to which MUFPA integrates structurally, in order to access information on current subsidies on development, in the Development Plan of the Federal University of Pará (PDI - 2016-2025) and Institutional Plan of the UFPA Museum, starting in 2003. In the final considerations, based on the general analysis of the micro and macro management structure based on the annual budget and other funds made available by the University and all the funding channels that the museum has for the realization of their projects, including the contribution of their association of friends, I highlight the observation of the potentialities and reliabilities of the promotion actions in the scope of museum management and the benefits that these actions bring to the institution.